"Pentingnya Kesehatan Mental” : Mengkaji Hubungan Kesehatan Mental Dengan Turnover Intention Pada Karyawan Generasi Milenial Di Perusahaan Startup - HASANAH, ROZIQOTUL; Mahadewi Sandiasih, Komang (Psikodinamika: Jurnal Literasi Psikologi, 2024)
This research aims to determine the relationship between mental health and turnover intention in millennial generation employees in startup companies. The hypothesis proposed in this research is that there is a negative relationship between mental health variables and turnover intention among millennial generation employees in startup companies. The respondents in this research were 55 millennial generation employees in startup companies spread across Java. The data collection method in this research uses two scales, namely the mental health scale and the turnover intention scale. Data analysis in this study used the Pearson Product Moment correlation analysis technique using the SPSS ver. 25 for windowsIt is important for startup companies to be able to pay attention to the mental health of their employees in order to increase productivity and maximize their performance towards the company's development. With full awareness of mental health, it will be able to effectively minimize the possibility of leaving the company to the employee. Keywords: Mental Health, Turnover Intention, Millennial Employees